6. Pengalaman Kerja Terhadap Kinerja Karyawan Ground Staff Maskapai Garuda Indonesia - Vidyana Mandrawaty (Jurnal Manajemen Dirgantara, 2018)
The purpose of this study is to find out whether the effect and how much work experience on employee performance.This research is a quantitative research using primary and secondary data. The method of collecting data uses a questionnaire distributed to employees of Garuda Indonesia airlines. Sampling Random Sampling that uses all members of the population and sample. Primary data is processed using SPSS 16 to determine the characteristics of respondents, simple linear regression test to determine the effect of work experience on employee performance. The results of these data researchers have the effect of work experience on employee performance. this is indicated by a significant value of P 0,000 <0,005, concluded that work experience has an effect on employee performance at t count 8.216. This shows that Ha is accepted, meaning that it has a positive and significant effect of work experience on employee performance by 64% and the remaining 36% is influenced by other researchers.